2010
DOI: 10.1038/jhh.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nebivolol in obese African Americans with hypertension (NOAAH): markers of inflammation and obesity in response to exercise-induced stress

Abstract: We sought to determine whether the antihypertensive drug nebivolol has beneficial effects on vascular markers of inflammation and oxidation in obese African-American patients with hypertension when exposed to exercise-induced stress. Forty-three obese, AfricanAmerican subjects with hypertension were treated with nebivolol (5-10 mg/day) for 8 weeks. Before treatment the subjects underwent an exercise treadmill study to a level of eight metabolic equivalents. Circulating levels of soluble interleukin-6 (sIL-6), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
(35 reference statements)
0
11
0
3
Order By: Relevance
“…25 Similar favorable effects on vascular markers of inflammation have lately been reported for nebivolol in obese hypertensive patients exposed to exercise-induced stress. 22 The choice of the non-dihydropyridine diltiazem as a representative CCB in this study was based primarily on the fact that the antiinflammatory effects of this CCB have not been previously studied. Moreover, patients who are treated with dihydropyridines have a high prevalence of peripheral edema in countries with warmer climates, such as Greece, whereas those treated with verapamil have a higher prevalence of constipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Similar favorable effects on vascular markers of inflammation have lately been reported for nebivolol in obese hypertensive patients exposed to exercise-induced stress. 22 The choice of the non-dihydropyridine diltiazem as a representative CCB in this study was based primarily on the fact that the antiinflammatory effects of this CCB have not been previously studied. Moreover, patients who are treated with dihydropyridines have a high prevalence of peripheral edema in countries with warmer climates, such as Greece, whereas those treated with verapamil have a higher prevalence of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,16 Antihypertensive treatment has been associated with beneficial effects on subclinical inflammation and thrombosis at rest and during exercise. [22][23][24][25][26] Nevertheless, comparative studies between different BPlowering agents have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their beneficial effects on blood pressure, nebivolol has a very strong anti-inflammatory and antioxidant potential. Nebivolol reduces the level of various oxidative and inflammatory markers like oxidized LDL, 8-isoprostanes, CRP, interleukin- (IL-) 6, adiponectin, leptin, intercellular adhesions molecule (ICAM-1), vascular cell adhesions molecule (VCAM-1), and tumor necrosis factor- α in various clinical studies [ 12 , 13 ]. However lab detection of these markers is costly and usually not performed on routine clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol and nebivolol have been demonstrated in both animal and human based studies to increase the bio-availability of nitric oxide [2, 4–6]. These two compounds have also been shown to exhibit beneficial effects on myocardial function by preventing hypertrophy [7, 8] as well as acting to decrease inflammation [9, 10] and oxidative stress [11, 12]. …”
Section: Introductionmentioning
confidence: 99%